#### Chemical Equations Balanced on 01/04/12

 Equations balanced on the previous day Equations balanced on the next day
 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313
Na + O = NaO2 =>
Na + 2 O = NaO2

Na2O2 + H2O = NaOH + O2 =>
2 Na2O2 + 2 H2O = 4 NaOH + O2

Al(NO3)3 + NaOH = Al(OH)3 + NaNO3 =>
Al(NO3)3 + 3 NaOH = Al(OH)3 + 3 NaNO3

CO2 + H2O = C6H12O6 + O2 =>
6 CO2 + 6 H2O = C6H12O6 + 6 O2

NaHCO3 = Na2CO3 + CO2 + H2O =>
2 NaHCO3 = Na2CO3 + CO2 + H2O

HCl + CaCO3 = CaCl2 + H2O + CO2 =>
2 HCl + CaCO3 = CaCl2 + H2O + CO2

Al(OH)3 + H2SO4 = Al2(SO4)3 + H2O =>
2 Al(OH)3 + 3 H2SO4 = Al2(SO4)3 + 6 H2O

Mg(OH)2 = MgO + H2O =>
Mg(OH)2 = MgO + H2O

KI + Pb2NO3 = Pb2I + KNO3 =>
KI + Pb2NO3 = Pb2I + KNO3

Ca(OH){2} + HCl = CaCl{2} + H2O =>
Ca(OH){2} + HCl = CaCl{2} + H2O

PCl5 + H2O = HCl + H3PO4 =>
PCl5 + 4 H2O = 5 HCl + H3PO4

KCl + Mg(OH)2 = KOH + MgCl2 =>
2 KCl + Mg(OH)2 = 2 KOH + MgCl2

Ca3(PO4)2 + H2SO4 = CaSO4 + Ca(H2PO4)2 =>
Ca3(PO4)2 + 2 H2SO4 = 2 CaSO4 + Ca(H2PO4)2

Al(OH)3 + H2SO4 = Al2(SO4)3 + H2O =>
2 Al(OH)3 + 3 H2SO4 = Al2(SO4)3 + 6 H2O

H2 + O2 = H2O =>
2 H2 + O2 = 2 H2O

KNO3 = KNO2 + O2 =>
2 KNO3 = 2 KNO2 + O2

Mg + N2 = Mg3N2 =>
3 Mg + N2 = Mg3N2

SeCl6 + O2 = SeO2 + Cl2 =>
SeCl6 + O2 = SeO2 + 3 Cl2

PCl5 + H2O = H3PO4 + HCl =>
PCl5 + 4 H2O = H3PO4 + 5 HCl

SiO2 + C = SiO + CO =>
SiO2 + C = SiO + CO

Ca3(PO4)2 + SiO2 + C = CaSiO3 + CO + P =>
Ca3(PO4)2 + 3 SiO2 + 5 C = 3 CaSiO3 + 5 CO + 2 P

Cu + H2SO4 = CuSO4 + H2O + SO2 =>
Cu + 2 H2SO4 = CuSO4 + 2 H2O + SO2

Mn(NO3)2 + NaBiO3 + HNO3 = Bi(NO3)2 + HMnO4 + NaNO3 + H2O =>
3 Mn(NO3)2 + 5 NaBiO3 + 9 HNO3 = 5 Bi(NO3)2 + 3 HMnO4 + 5 NaNO3 + 3 H2O

SiO2 + C = SiO + CO =>
SiO2 + C = SiO + CO

Na + MgF2 = NaF + Mg =>
2 Na + MgF2 = 2 NaF + Mg

PCl5 + H2O = H3PO4 + HCl =>
PCl5 + 4 H2O = H3PO4 + 5 HCl

C8H18 + O2 = CO2 + H2O =>
2 C8H18 + 25 O2 = 16 CO2 + 18 H2O

Na + Cl2 = NaCl =>
2 Na + Cl2 = 2 NaCl

Mg + HC2H3O2 = Mg(C2H3O2)2 + H2 =>
Mg + 2 HC2H3O2 = Mg(C2H3O2)2 + H2

C2H6 + O2 = CO2 + H2O =>
2 C2H6 + 7 O2 = 4 CO2 + 6 H2O

Fe2O3 + H2 = Fe + H2O =>
Fe2O3 + 3 H2 = 2 Fe + 3 H2O

H2S + Cl2 = S8 + HCl =>
8 H2S + 8 Cl2 = S8 + 16 HCl

K + MgBr2 = KBr + Mg =>
2 K + MgBr2 = 2 KBr + Mg

Al2O3 = Al + O2 =>
2 Al2O3 = 4 Al + 3 O2

C2H2 + O2 = CO2 + H2O =>
2 C2H2 + 5 O2 = 4 CO2 + 2 H2O

Hg(OH)2 + H3PO4 = Hg3(PO4)2 + H2O =>
3 Hg(OH)2 + 2 H3PO4 = Hg3(PO4)2 + 6 H2O

SiO2 + C = SiO + CO =>
SiO2 + C = SiO + CO

Fe + H2SO4 = Fe(SO4)3 + H2 =>
Fe + 3 H2SO4 = Fe(SO4)3 + 3 H2

MgCO3 = MgO + CO2 =>
MgCO3 = MgO + CO2

Fe + O2 = Fe2O3 =>
4 Fe + 3 O2 = 2 Fe2O3

Zn + H2SO4 = ZnSO4 + H2 =>
Zn + H2SO4 = ZnSO4 + H2

Cu + HNO3 = Cu(NO3)2 + NO2 + H2O =>
Cu + 4 HNO3 = Cu(NO3)2 + 2 NO2 + 2 H2O

Hg2O + O2 = HgO =>
2 Hg2O + O2 = 4 HgO

SiCl4 = Si + Cl2 =>
SiCl4 = Si + 2 Cl2

Na + Br2 = NaBr =>
2 Na + Br2 = 2 NaBr

C6H12O6 + O2 = CO2 + H2O =>
C6H12O6 + 6 O2 = 6 CO2 + 6 H2O

CO2 + H2O = C6H12O6 + O2 =>
6 CO2 + 6 H2O = C6H12O6 + 6 O2

H2O = H2 + O2 =>
2 H2O = 2 H2 + O2

Fe + H2O = Fe3O4 + H2 =>
3 Fe + 4 H2O = Fe3O4 + 4 H2

NH4Cl + Hg(ClO3)2 = NH4ClO3 + HgCl2 =>
2 NH4Cl + Hg(ClO3)2 = 2 NH4ClO3 + HgCl2

 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 146 147 148 149 150 151 152 153 154 155 156 157 158 159 160 161 162 163 164 165 166 167 168 169 170 171 172 173 174 175 176 177 178 179 180 181 182 183 184 185 186 187 188 189 190 191 192 193 194 195 196 197 198 199 200 201 202 203 204 205 206 207 208 209 210 211 212 213 214 215 216 217 218 219 220 221 222 223 224 225 226 227 228 229 230 231 232 233 234 235 236 237 238 239 240 241 242 243 244 245 246 247 248 249 250 251 252 253 254 255 256 257 258 259 260 261 262 263 264 265 266 267 268 269 270 271 272 273 274 275 276 277 278 279 280 281 282 283 284 285 286 287 288 289 290 291 292 293 294 295 296 297 298 299 300 301 302 303 304 305 306 307 308 309 310 311 312 313